A three-dimensional computational model of H2-air premixed combustion in non-circular micro-channels for a thermo-photovoltaic (TPV) application - Akhtar, S. (Elsevier Ltd, 2015)
Wall temperature uniformity and enhancement in a micro combustor for thermo photovoltaic (TPV) applications have attracted considerable attention from researchers in recent years because of their direct impact on efficiency and feasibility of desired energy conversion. In this regard, numerous experimental and numerical studies in micro-combustion application have been conducted and reported. However, most previous studies have been focused on geometrical configurations limited to planar and circular channels. It is therefore of interest to investigate the impact of different channel geometries on wall temperature distribution and energy conversion efficiency. This study addresses flow and flame behavior in a micro-combustor. By utilizing the well-established computational fluid dynamics (CFD) approach, the effect of geometrical parameters on the flow behavior and wall temperature is examined and evaluated. In order to improve the productive capability of the computational model, several steady state Reynolds Average Numerical Simulation (RANS) turbulence models alongside with different reaction rate formulations are evaluated. The results indicate that Reynolds Stress Model (RSM) with Eddy Dissipation Concept (EDC) provide the best quantitative prediction. The developed model is employed to investigate the effect of inlet velocity on flame structure and outer wall temperature. Furthermore, the effect of reactor cross sections, including circular, square, rectangular, triangular and trapezoidal, on the wall temperature is also evaluated. The results show that the wall temperature is increased with an increase in the inlet velocity. Trapezoidal and triangular cross-sections are found to have better performance in terms of Figure of Merit (FoM), a parameter used in this study to gage thermal and hydraulic performance of a micro-combustor. Â© 2015 Elsevier Ltd.